Bisphosphonate enhances TRAIL sensitivity to human osteosarcoma cells via death receptor 5 upregulation - Moon, Myung-Hee; Jeong, Jae-Kyo; Seo, Jae-Suk; Seol, Jae-Won; Lee, You-Jin; Xue, Meilang; Jackson, Christopher J; Park, Sang-Youel (Experimental & molecular medicine, 2011)
Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), a member of the TNF superfamily of cytokines, is one of the most promising candidates for cancer therapeutics. However, many osteosarcomas are resistant to TRAIL. Bisphosphonates are very effective in the treatment of bone problems associated with malignancies; the antitumor effects are due to the inhibition of protein prenylation that is essential for cell function and survival. The purpose of this study was to determine the effects of bisphosphonates on TRAIL-resistant MG 63 human osteosarcoma cells. The cells showed no response to TRAIL alone; however, pre-treatment with bisphosphonates significantly increased TRAIL-mediated apoptosis and cellular activation of caspase-3. Bisphosphonates significantly induced mRNA and protein expression of the TRAIL receptor, DR5. Bisphosphonates induced protein unprenylation in MG 63 cells; in addition, co-treatment with TRAIL also significantly increased protein unprenylation. Blocking of protein unprenylation using geranylgeraniol attenuated the cellular responses, including cell apoptosis and protein unprenylation induced by bisphosphonates and TRAIL. This is the first study to demonstrate that bisphosphonates markedly enhanced TRAIL-induced apoptosis in human osteosarcoma cells. These findings suggest that bisphosphonates may be a new and effective anticancer treatment with TRAIL proteins for TRAIL-resistant cancer cells.